2003
DOI: 10.1016/j.str.2003.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Interactions of NCAM Ig1-2-3 Suggest a Novel Zipper Mechanism for Homophilic Adhesion

Abstract: The neural cell adhesion molecule, NCAM, mediates Ca(2+)-independent cell-cell and cell-substratum adhesion via homophilic (NCAM-NCAM) and heterophilic (NCAM-non-NCAM molecules) binding. NCAM plays a key role in neural development, regeneration, and synaptic plasticity, including learning and memory consolidation. The crystal structure of a fragment comprising the three N-terminal Ig modules of rat NCAM has been determined to 2.0 A resolution. Based on crystallographic data and biological experiments we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
224
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(238 citation statements)
references
References 49 publications
13
224
0
1
Order By: Relevance
“…The intracellular domain of NCAM directly interacts with the spectrin scaffold accumulating in synapses (25,35). The extracellular domain of NCAM binds to the extracellular domains of NCAM molecules on adjacent membranes, thereby mediating homophilic cell adhesion interactions (48). In the present study, we found that disruption of the association of NCAM180 with the cytoskeleton reduces its accumulation in the postsynaptic membrane.…”
Section: Discussionsupporting
confidence: 57%
“…The intracellular domain of NCAM directly interacts with the spectrin scaffold accumulating in synapses (25,35). The extracellular domain of NCAM binds to the extracellular domains of NCAM molecules on adjacent membranes, thereby mediating homophilic cell adhesion interactions (48). In the present study, we found that disruption of the association of NCAM180 with the cytoskeleton reduces its accumulation in the postsynaptic membrane.…”
Section: Discussionsupporting
confidence: 57%
“…A number of Ig3-specific reagents have been reported to inhibit cellcell aggregation including antibodies, recombinant proteins, and peptides, and it has been proposed that self-association of the Ig3 domains is central to N-CAM binding (15)(16)(17)(18). However, we and others (3,19) have been unable to demonstrate self-association of the isolated Ig3 domain in solution. To evaluate the contribution of Ig3 to N-CAM homophilic binding, we produced recombinant Fc fusion proteins corresponding to just the N-terminal domain, Ig1, the N-terminal two domains, Ig12, and the N-terminal three domains, Ig123 (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…The crystal structures of dimeric Ig12 and Ig123 identified the intercalation of Phe 19 into a pocket on the surface of Ig2 as a prominent feature of the interaction (19,20). Here, we have employed this point mutation to probe the role of the Ig12 interaction in N-CAM-mediated bead aggregation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural evidence suggests that NCAM molecules form cis dimers in the cell membrane and these cis dimers mediate trans interactions between cells via formation of two-dimensional zippers [12,13]. In neurons the extracellular part of NCAM has been shown to bind and mediate phosphorylation/activation of the fibroblast growth factor receptor (FGFR) [14,15].…”
Section: Introductionmentioning
confidence: 99%